Simple and sensitive HPLC-UV method for determination of bexarotene in rat plasma - Lee, Jong Bong; Zgair, Atheer; Kim, Tae Hwan; Kim, Min Gi; Yoo, Sun Dong; Fischer, Peter M.; Gershkovich, Pavel (Elsevier, 2017)
Bexarotene is currently marketed for treatment of cutaneous T-cell lymphoma and there has been growing interest in its therapeutic effectiveness for other cancers. Neuroprotective effects of bexarotene have also been reported. In this study, a simple, sensitive and cost-efficient bioanalytical method for determination of bexarotene in rat plasma was developed and fully validated. The method utilises protein precipitation with acetonitrile and liquid-liquid extraction with n-hexane-ethyl acetate (10:1, v/v). An HPLC-UV system with a Waters Atlantis C18 column and a mobile phase of acetonitrile-ammonium acetate buffer (10 mM, pH 4.1) at a ratio of 75:25 (v/v), flow rate 0.2 mL/min was used. Chromatograms were observed by a UV detector with wavelength set to 259 nm. Intra- and inter-day validations were performed and sample stability tests were conducted at various conditions. The applicability of the method was demonstrated by a pharmacokinetic study in rats. Intravenous bolus dose of 2.5 mg/kg was administered to rats and samples were obtained at predetermined time points. As a result, pharmacokinetic parameters of AUCinf (4668 ± 452 h ng/mL), C0 (6219 ± 1068 ng/mL) and t1/2 (1.15 ± 0.02 h) were obtained. In addition, the developed method was further applied to human and mouse plasma to assess the suitability of the method for samples from other species.